2018
DOI: 10.1016/j.cortex.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

The role of left insula in executive set-switching: Lesion evidence from an acute stroke cohort

Abstract: Impairments in executive functions are common in stroke survivors, both in the acute and in the chronic phase. However, little is known about the underlying lesion neuroanatomy of these deficits. This study aimed to elucidate the pattern of brain damage underlying executive dysfunction in a large and acute stroke cohort. Executive set-switching deficits were evaluated by a shape-based analogue of the Trail Making Test (from the Oxford Cognitive Screen) in a consecutive sample of 144 stroke patients (age: 70 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 48 publications
1
23
0
1
Order By: Relevance
“… 37 ± 11 years Chronic (3 ± 3 years) Standard TMT VLSM of TMT-B raw completion time. Left dorsomedial prefrontal Varjacic et al (2017) 144 Stroke (ischemic and haemorrhagic) Left (N = 47); Right (N = 60); Bilateral (N = 37). 71 ± 15 years Acute (5 ± 4 days) TMT analogue from Oxford Cognitive Screen (OCS) VLSM of accuracy score on the set-switching condition Left insula …”
Section: Lesion-symptom Mapping Studies In Patients With Brain Damagementioning
confidence: 99%
See 1 more Smart Citation
“… 37 ± 11 years Chronic (3 ± 3 years) Standard TMT VLSM of TMT-B raw completion time. Left dorsomedial prefrontal Varjacic et al (2017) 144 Stroke (ischemic and haemorrhagic) Left (N = 47); Right (N = 60); Bilateral (N = 37). 71 ± 15 years Acute (5 ± 4 days) TMT analogue from Oxford Cognitive Screen (OCS) VLSM of accuracy score on the set-switching condition Left insula …”
Section: Lesion-symptom Mapping Studies In Patients With Brain Damagementioning
confidence: 99%
“…An association was found between circumscribed lesion sites within the right dorsolateral prefrontal cortex and TMT-B sequencing and shifting errors, respectively. In the second VLSM study, acute stroke patients without hemi-spatial neglect ( Varjacic et al, 2017 ) performed the TMT analogue of the Oxford Cognitive Screen (OCS, Demeyere et al, 2015 ), which is an optimised test battery for the cognitive assessment of stroke patients. Specifically, participants were asked to connect large-to-small target shapes embedded in an array of non-target shape distractors (baseline condition, analogous to TMT-A) and to connect large-to-small target shapes in an alternating fashion (set-switching condition, analogous to TMT-B).…”
Section: Lesion-symptom Mapping Studies In Patients With Brain Damagementioning
confidence: 99%
“…Task-based fMRI studies have shown significantly increased activation during TMT B versus TMT A within the left precentral gyrus (Moll, Oliveira-Souza, Moll, Bramati, & Andreiuolo, 2002) and the insula (Zakzanis, Mraz, & Graham, 2005). Additionally, a voxel-based lesion-symptom mapping study reported a negative association between lesions within the left insular cortex and a TMT task accuracy score, which like the TMT B minus A score attenuates the influence of processing speed and reflects cognitive flexibility (Varjačić et al, 2018). Like the TMT B score, the TMT B minus A is also correlated with atrophy of the bilateral medial temporal lobes (Oosterman et al, 2010).…”
Section: Visual Attention and Cognitive Flexibilitymentioning
confidence: 99%
“…While grouping patients with different aetiologies is likely to suffer from potential confounds, it remains necessary to obtain large groups of patients to investigate cognitive impairments (for similar approaches see Aridan, Pelletier, Fellows, & Schonberg, 2019;Aron, Monsell, Sahakian, & Robbins, 2004;Gläscher et al, 2012;Roca et al, 2010;Stamenova et al, 2017;Stuss et al, 2005;Thompson-Schill et al, 1998;Urbanski et al, 2016). Some other studies favour the use of a single aetiology (e.g., Baldo, Schwartz, Wilkins, & Dronkers, 2006;Campanella et al, 2016;Sperber & Karnath, 2017;Varjačić et al, 2018). However, there is no consensus in the field of neuropsychology regarding what is the best approach to adopt.…”
Section: Discussionmentioning
confidence: 99%